Homo Crispr and the Uncanny Art of Self-Reproduction - Mohr, Dunja M. (Journal of Posthumanism, 2024)
Selected classic 19th- and 20th-century fictional texts, I argue, function as imaginative precursors of material fusions, either by prosthetic integration in the sense of repurposed imperfection or by internalizing genetic perfection, creating homo crispr. E.T.A. HOFFMANN’s dark literary tale The Sandman (1816), MARY SHELLEY’s gothic proto-science fiction Frankenstein (1818), VILLIER DE L’ISLE-ADAM’s fin de siècle Tomorrow’s Eve (1886), and ANGELA CARTER’s carnivalesque The Passion of New Eve (1977) position the artificial other as both an externalization of the human desire for perfection in an uncanny act of autoerotic, poetic-scientific self-fertilization and as a reverse image of the composite self.